Low-frequency vibrational modes in G-quadruplexes reveal the mechanical properties of nucleic acids - González-Jiménez, Mario; Ramakrishnan, Gopakumar; Wynne, Klaas (bioRxiv, 2020)
Low-frequency vibrations play an essential role in biomolecular processes involving DNA such as gene expression, charge transfer, drug intercalation, and DNA-protein recognition. However, understanding of the vibrational basis of these mechanisms relies on theoretical models due to the lack of experimental evidence. Here we present the low-frequency vibrational spectra of G-quadruplexes (structures formed by four strands of DNA) and B-DNA characterized using femtosecond optical Kerr-effect spectroscopy. Contrary to expectation, we found that G-quadruplexes show several strongly underdamped delocalized phonon-like modes that have the potential to contribute to the biology of the DNA at the atomic level. In addition, G-quadruplexes present modes at a higher frequency than B-DNA demonstrating that changes in the stiffness of the molecule alter its gigahertz to terahertz vibrational profile. These results demonstrate that current theoretical models fail to predict basic properties of the vibrational modes of DNA.